A Peningkatan Kemampuan Membaca Permulaan Anak Usia 5-6 Tahun Melalui Permainan Scrabble: Peningkatan Kemampuan Membaca Permulaan Anak Usia 5-6 Tahun Melalui Permainan Scrabble - Salsabilla Riyanti (IKIP Siliwangi, 2024)
The aim of this research is to obtain data on improving the initial reading abilities of children aged 5-6 years through Scrabble games held at RA Nurul Yaqin. The research subjects were students aged 5-6 years at RA Nurul Yaqin with a total of 15 children consisting of 7 boys and 8 girls. Kemmis and Mc model PTK. Taggart was used in this research through the stages of planning, implementation, observation and reflection. Data collection techniques in this research use observation, interviews and documentation. Data analysis uses the formula for average value, maximum score and percentage. The results of the research showed that the results of pre-cycle observations reached a percentage of 48%, which shows that initial reading ability was still low, so action was needed in cycle I. Children experienced an increase in cycle I until they got a percentage of 59%, because the results did not meet the researchers' expectations, namely 80%. action is taken in cycle II. In cycle II there was a good increase, cycle II got a percentage of 81% so it was found that the results of the activities carried out were successful in achieving the target.